Pompa Air Menggunakan Putaran Motor Matic Untuk Pengairan Pertanian Di Kelompok Tani Beruntung - Wijayanto, Jarot; Murdjani; Barry, Akmal (LPPM IST AKPRIND Yogyakarta, 2023)
ommunity service activities in this program involve partners from the Lucky Farmers Group in the Penjambuan Village area, Sungai Tabuk District, Banjar Regency. Implementation of activities held in the area of agricultural land. The service begins with the procurement of centrifugal pumps and automatic motors to take advantage of the rotation of the engine along with the necessary equipment, to be assembled and then carry out counseling on the use and maintenance of the water pump machine.The results of this community service program are very useful for Penjabuan Village, Sungai Tabuk District, Banjar Regency because by procuring a water pump from an automatic motor, it provides a solution to problems in partners, namely the Lucky Farmers Group to be able to drive horticultural agriculture in a sustainable manner, not relying on rain-fed and can provide equipment water pump to help prevent peatland fires around the area.